2019
DOI: 10.5513/jcea01/20.1.2159
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of bulk density in Croatian forest Pseudogleys based on contents of soil organic matter and clay

Abstract: Soil bulk density (BD) is often used to assess soil properties related to soil structure and general soil quality, or to convert weight units to volume/area units. Because collecting undisturbed soil samples (cores) and directly measuring BD is laborious and time-consuming, data on BD are often lacking. Pedotransfer functions (PTFs) can be used to predict BD from more readily available (easily measured) properties. However, specific PTFs for specific range of soils should be developed. In this study, soil orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
1
0
0
Order By: Relevance
“…Agustina et al (2016) reported that the amount of clay increased along with the increase in soil depth was found in the forest land. In addition, the positive correlation between BD and clay content was also found from the previous research conducted in Croatia forest, the western edge of the Pannonia Basin by Rubinić and Safner (2019), which means that the addition of clay is accompanied by an increase in soil BD. Soil chemical properties at various depth in the forest land was mainly comparable (Table 2) among slope positions (i.e.…”
Section: Resultssupporting
confidence: 80%
“…Agustina et al (2016) reported that the amount of clay increased along with the increase in soil depth was found in the forest land. In addition, the positive correlation between BD and clay content was also found from the previous research conducted in Croatia forest, the western edge of the Pannonia Basin by Rubinić and Safner (2019), which means that the addition of clay is accompanied by an increase in soil BD. Soil chemical properties at various depth in the forest land was mainly comparable (Table 2) among slope positions (i.e.…”
Section: Resultssupporting
confidence: 80%